Experimental analysis of crack width movement of continuously reinforced concrete railway track. (1st September 2019) - Cho, Young Kyo; Kim, Seong-Min
Highlights: Crack width movements in CRCT under temperature changes were measured in situ. Contraction and reflection crack width movements were comprehensively analyzed. Comparisons were made between contraction and reflection crack behaviors. Relationship between crack width movements and transverse locations was evaluated. Suggestions to improve CRCT performance concerning crack widths were proposed. Abstract: This study investigated the crack width movements of a continuously reinforced concrete track (CRCT) of railways subjected to environmental loads, such as changes in temperature. To this end, in-situ experiments were carried out at two railway CRCT sections. There are two different types of cracks in CRCT namely the contraction (top-down) crack and reflection (bottom-up) crack. The behaviors of the contraction and reflection cracks were thoroughly analyzed and the differences in the crack width movements were investigated. The relationship between crack width movements and transverse locations was also evaluated. Based on the findings from this comprehensive experimental study of crack widths, we proposed multiple methods to improve the performance of CRCT.